1982
DOI: 10.1128/jcm.16.3.490-494.1982
|View full text |Cite
|
Sign up to set email alerts
|

Controlled evaluation of hypertonic sucrose medium for detection of bacteremia and fungemia in supplemented peptone broth

Abstract: Because the value of hypertonic media in detection of bacteremia and fungemia is controversial, we evaluated supplemented peptone broth (SPB) with 0.03% sodium polyanetholsulfonate with and without 10% sucrose in 5,439 paired blood cultures from adult patients. The aerobic atmosphere, 1:10 ratio of blood to broth, and methods for processing blood cultures were identical. Only cultures with adequate blood samples (-4 ml) were compared statistically. More clinically important bacteria were recovered from SPB wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

1983
1983
1994
1994

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…Not only staphylococci but also Escherichia coli and Enterobacter aerogenes grew better in the hypertonic medium. Similar sucrose-containing media were found to be advantageous by some investigators (20,21,26) but not by others (8,24). Henrichsen and Brunn (12) also observed selective growth in the hypertonic medium.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Not only staphylococci but also Escherichia coli and Enterobacter aerogenes grew better in the hypertonic medium. Similar sucrose-containing media were found to be advantageous by some investigators (20,21,26) but not by others (8,24). Henrichsen and Brunn (12) also observed selective growth in the hypertonic medium.…”
Section: Discussionmentioning
confidence: 89%
“…BACTEC offers the option of either a two-medium system (for aerobic and anaerobic microorganisms) or a three-medium system, including one medium with 10% sucrose (hypertonic medium). The value of the osmotically stabilized medium has been examined in both the BACTEC system (4, 14, 21) and a nonradiometric system (8,9,19,24,26), but the results are still controversial.…”
mentioning
confidence: 99%
“…Given the widely discrepant results in multiple wellcontrolled studies of hypertonic versus isotonic blood cul- ture media, it seems reasonable to conclude that the potential value of hypertonic broth depends at least in part upon the medium to which it has been added. There may be value in using hypertonic supplemented peptone broth (11,18) or Columbia broth (3), but the value of hypertonic TSB is more difficult to assess. At the Mayo Clinic, several studies have shown either no advantage or a disadvantage with use of hypertonic TSB (5,13,16).…”
Section: Discussionmentioning
confidence: 99%
“…The potential utility of hypertonic blood culture broths for the detection of bacteremia and fungemia remains controversial. Some well-controlled clinical studies have demonstrated that the addition of sucrose to a blood culture broth enhances the yield or speed of detection of microorganisms compared with the yield or speed of an isotonic version of the same broth (1,3,4,6,11,18), whereas other reports have shown no advantage or a disadvantage associated with hypertonic media (5,10,13,15). Some authors have suggested that hypertonic media are useful only with selected patients (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation